Effect of Bone Marrow Stromal Cells in Parkinson's Disease Rodent Model: A Meta-Analysis - Liu, Jianyang; He, Jialin; Huang, Yan; Hu, Zhiping (Frontiers in Aging Neuroscience, 2020)
Background: Bone marrow stromal cells (BMSCs) has been reported to have beneficial effects in improving behavioral deficits, and rescuing dopaminergic neuron loss in rodent models of Parkinson's disease (PD). However, their pooled effects for dopaminergic neuron have yet to be described. Objective: To review the neuroprotective effect of naïve BMSCs in rodent models of PD. Methods: The PubMed, EMBASE, and Web of Science databases were searched up to September 30, 2020. Inclusion criteria according to PICOS criteria were as follows: (1) population: rodents; (2) intervention: unmodified BMSCs; (3) comparison: not specified; (4) primary outcome: tyrosine hydroxylase level in the substantia nigra pars compacta and rotational behavior; secondary outcome: rotarod test, and limb function; (5) study: experimental studies. Multiple prespecified subgroup and meta-regression analysis were conducted. Following quality assessment, random effects models were used for this meta-analysis. Results: Twenty-seven animal studies were included. The median quality score was 4.7 (interquartile range, 2–8). Overall standardized mean difference between animals treated with naïve BMSCs and controls was 2.79 (95% confidence interval: 1.70, 3.87; P < 0.001) for densitometry of tyrosine hydroxylase-positive staining; −1.54 (95% confidence interval: −2.11, −0.98; P < 0.001) for rotational behavior. Significant heterogeneity among studies was observed. Conclusions: Results of this meta-analysis suggest that naïve BMSCs therapy increased dopaminergic neurons and ameliorated behavioral deficits in rodent models of PD.